Civic Budget as a Potential Source of Financing of Real Estate - Agnieszka Wójcik (Barometr Regionalny)
The subject of this article is the role of the civic budget as a potential source of financing of real estate. The topic has been presented both in quantitative terms (the structure of proposals that were submitted for voting, average values, and trends) and in qualitative terms (the types of real estate). The aim of this article is to verify the hypothesis that the participatory budget is treated as a potential source of real estate financing (i.e., for projects with limited usability). For this purpose, 1703 projects, submitted to a vote in the years 2014–2017 have been examined.